Students’ Perceptions of Using Online Learning Environment in Writing Class During Pandemic Covid-19 - Nurhasanah, Nurhasanah; Sulistyo, Bambang (FKIP Universitas Lampung, 2022)
Student’s Perception of Using Online Learning Environment in Writing Class During Pandemic Covid-19. This study aims to analyses students’ perception of using online learning in writing class during pandemic covid 19. The method used in this research is descriptive The subject of this research was 51 students of English Education Study Progra which only took in semester 2 and 4. The result of this research in indicator of students’ participation with mean score 3,68 in high category. In indicator effect of online learning with mean score 3,67 in high category. In indicator teacher’s role as facilitator with mean score 3,61 in medium category. In indicator of social context with mean score 3,72 in high category. The cocnlucion this research is majority of students agree that in pandemic situation online learning is a facility that can be used in learning process especially in writing class. Kata kunci: perception, online learning, writing class.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202211